Qalhāt - Bhacker, Mohammed Reda; Bhacker, Bernadette (Encyclopaedia of Islam Three Online, 2024)
Keywords: Oman – Histoire

The Kanem and Borno Sultanates (11th–19th Centuries) - Dewière, Rémi (Oxford Research Encyclopedia of African History, 2024)
"The Kanem and Borno Sultanates (11th–19th Centuries)" published on by Oxford University Press.
Keywords: Tchad – Histoire

Barghash : sultan of Zanzibar (Encyclopaedia Britannica, 2024)
Barghash was the sultan of Zanzibar (1870–88), a shrewd and ambitious ruler, who, for most of his reign, looked to Britain for protection and assistance but eventually saw his domains divided between Germany and his former protector. Although not the first heir to the throne of his father, Saʿīd
Keywords: Biographies – Zanzibar